2010
DOI: 10.4248/ijos10065
|View full text |Cite
|
Sign up to set email alerts
|

Squamous Papilloma: Case Report and Review of Literature

Abstract: Squamous papillomas are common lesions of the oral mucosa with a predilection for the mucosa of the hard and soft palate. As an oral lesion, it raises concern because of its clinical appearance, which may mimic exophytic carcinoma, verrucous carcinoma or condyloma acuminatum. Its pathogenesis is related to human papilloma virus but there is controversy regarding its viral origin. We present a case of squamous papilloma presenting as oral lesion along with a review of the literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
78
0
16

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(98 citation statements)
references
References 7 publications
4
78
0
16
Order By: Relevance
“…SP can be further divided into several types: isolated, solitary and multiple-recurring (11). The findings observed in this study showed that lesion development (about 7 months), in the lingual site as the most frequent and round lesion.…”
Section: Discussionmentioning
confidence: 67%
See 3 more Smart Citations
“…SP can be further divided into several types: isolated, solitary and multiple-recurring (11). The findings observed in this study showed that lesion development (about 7 months), in the lingual site as the most frequent and round lesion.…”
Section: Discussionmentioning
confidence: 67%
“…It can be granular, fingerlike and may be asymptomatic. (11). In this case both lesions were clinically considered verrucous, vegetative and sessile.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These types of growths appear as pink to white, measuring <1 cm in range and shows characteristic cauliflower-like surface alterations. [4] Studies have showed that high-risk HPVs are most commonly found in close proximity to tongue and oropharynx and periodontium of patients with chronic periodontitis. [5] In present case report, the site of occurrence is gingiva involving attached gingiva and alveolar mucosa on lingual aspect of the mandibular jaw with respect to 36-37.…”
Section: Discussionmentioning
confidence: 99%